2014 IEEE Symposium on Computational Intelligence in Biometrics and Identity Management (CIBIM) 2014
DOI: 10.1109/cibim.2014.7015445
|View full text |Cite
|
Sign up to set email alerts
|

A new wrist vein biometric system

Abstract: In this piece of work a wrist vein pattern recognition and verification system is proposed. Here the wrist vein images from the PUT database were used, which were acquired in visible spectrum. The vein image only highlights the vein pattern area so, segmentation was not required. Since the wrist's veins are not prominent, image enhancement was performed. An Adaptive Histogram Equalization and Discrete Meyer Wavelet were used to enhance the vessel patterns. For feature extraction, the vein pattern is characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 15 publications
0
20
1
Order By: Relevance
“…The reported EER is 1.23 %. However, based on the ROC curves provided in [11], the FNMR values for FMR≤0.1% are higher comparing to our results.…”
Section: Methodscontrasting
confidence: 78%
See 2 more Smart Citations
“…The reported EER is 1.23 %. However, based on the ROC curves provided in [11], the FNMR values for FMR≤0.1% are higher comparing to our results.…”
Section: Methodscontrasting
confidence: 78%
“…The paper [11], to the best of our knowledge, is the only one reporting recognition results using PUT Vein database. However, the precise evaluation protocol is unknown.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to texture-oriented feature representation, [49] employs a preprocessing consisting of adaptive histogram equalisation and enhancement using a discrete Meyer wavelet. Subsequently, LBP is extracted from patches with subsequent BoF representation in a spatial pyramid.…”
Section: Wrist Vein Recognition Toolchainmentioning
confidence: 99%
“…For the preprocessing approach, discretely implemented Meyer wavelet and histogram equalization with adaptive capability were proposed feature extraction using Pattern of Dense Local Binary known as D-LBP showed that it was able to achieve (EER) or the rate of an equal error on 0.79 [23]. Regarding this reason, it is intended to develop a wrist recognition system which is better than that of the D-LBP.…”
Section: A Related Workmentioning
confidence: 99%